2020
DOI: 10.1101/2020.08.31.275107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CRISPR screens in physiologic medium reveal conditionally essential genes in human cells

Abstract: SUMMARYForward genetic screens across hundreds of diverse cancer cell lines have started to define the genetic dependencies of proliferating human cells and how these vary by genotype and lineage. Most screens, however, have been carried out in culture media that poorly resemble metabolite availability in human blood. To explore how medium composition influences gene essentiality, we performed CRISPR-based screens of human cancer cell lines cultured in traditional versus human plasma-like medium (HPLM). Sets o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 86 publications
(114 reference statements)
0
25
0
Order By: Relevance
“…Many cancer cell types increase glutamine utilization to support the TCA cycle and fatty acid biosynthesis in vitro (Metallo et al, 2012;Mullen et al, 2012); however reproducing this phenotype in vivo has generated mixed results (Davidson et al, 2016;Le et al, 2012;Son et al, 2013;Tardito et al, 2015). One potential explanation for this discrepancy is the difference in nutrient profile of cell culture media compared to in vivo microenvironments (Ackermann and Tardito, 2019;Rossiter et al, 2021;Voorde et al, 2019). Plasma and interstitial fluid contain metabolites that impact cellular metabolism but are routinely excluded from most cell culture medias.…”
Section: Discussionmentioning
confidence: 99%
“…Many cancer cell types increase glutamine utilization to support the TCA cycle and fatty acid biosynthesis in vitro (Metallo et al, 2012;Mullen et al, 2012); however reproducing this phenotype in vivo has generated mixed results (Davidson et al, 2016;Le et al, 2012;Son et al, 2013;Tardito et al, 2015). One potential explanation for this discrepancy is the difference in nutrient profile of cell culture media compared to in vivo microenvironments (Ackermann and Tardito, 2019;Rossiter et al, 2021;Voorde et al, 2019). Plasma and interstitial fluid contain metabolites that impact cellular metabolism but are routinely excluded from most cell culture medias.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic dependencies of a cancer cell can be markedly altered by in vitro versus in vivo growth conditions (Rossiter et al 2020), particularly the requirement for cell surface receptors and metabolic enzymes whose function is influenced by the extracellular microenvironment. This issue provided the rationale for developing a robust screening method for interrogating genetic dependencies of human AML cells grown in vivo.…”
Section: A Domain-focused Crispr Screening Methods For Identifying In Vivo-relevant Aml Dependenciesmentioning
confidence: 99%
“…Furthermore, recent studies have shown that cell culture media impacts genetic dependencies observed in CCLs (Cheteh et al , 2017; Li et al , 2019; Rossiter et al , 2021). Nevertheless, despite the lack of immune‐like cells or cancer fibroblasts, it was found that specific metabolites in human plasma‐like medium also influence the set of essential genes in CCLs detected in CRISPR‐based screens (Rossiter et al , 2021). Co‐culturing CCLs with cancer‐associated fibroblasts (CAF) or even CAF‐conditioned medium reduced response to chemotherapeutic treatments and conversely increased cell survival in prostate CCLs (Cheteh et al , 2017).…”
Section: Factors That Might Compromise How Well Cell Lines Represent ...mentioning
confidence: 99%